Orbital Tumor Misdiagnosed as Optic Neuritis in Rheumatoid Arthritis Patient: A Case Report: Poster Presentation - Case Report - General practitioner - Marcellina; Maria L. Susyono (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Unilateral blurred vision and optic nerve swelling are the two most common signs of optic neuritis (ON). However, ON is rarely reported in patients with rheumatoid arthritis (RA), thus necessitating further diagnostic workup. Case Illustration : A 42-year-old woman visited our hospital with strabismus and progressive loss of vision in her left eye since three months ago. She had been treated with pulse dose steroid for suspected ON. She had been diagnosed with RA over five years and treated with immunomodulatory medication. Left eye examination revealed best corrected visual acuity of 20/50, proptosis, esotropia with painless limitation in temporal movement. Afferent pupillary defect (RAPD) and optic nerve swelling were present. OCT assessment revealed reduction in RNFL thickness. Further magnetic resonance imaging (MRI) investigation revealed a 2.35 x 2.6 x 1.8 cm mass in the left intraconal retrobulbar, in proximity to the medial optic nerve, which suggests a case of orbital Schwanoma. Excisional biopsy was performed and revealed a benign tumor. Discussion : Intraconal tumor may falsely be diagnosed as an optic neuritis in autoimmune patient. Neuro- ophthalmologic symptoms of systemic inflammatory in the optic nerve includes unilateral acute visual loss and pain in eye movement. Signs of ON includes RAPD, disc edema, and corresponding visual field defect. MRI of the optic nerve can assist diagnostic workup. Conclusion : The exact diagnosis of rheumatoid arthritis-associated ocular manifestations is challenging. Imaging using MRI might be needed to provide clarity in the diagnosis.